2024
DOI: 10.1039/d3mh01039b
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature reversible F-ion batteries based on sulfone electrolytes with a mild anion acceptor additive

Yifan Yu,
Meng Lei,
Chilin Li

Abstract: A non-boron anion acceptor with moderate Lewis acidity is proposed to prepare a F-ion electrolyte with high conductivity at the mS cm−1 level at room temperature. A fluoride ion battery is successfully operated with high conversion reaction reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Therefore, the F − transference number would be higher than 0.5. 6,23 This is consistent with the higher partial conductivity of F − anions than that of TMA + cations, as predicted by theoretic calculations (Table S1). In concentrated electrolytes, the movement of both TMA + cations and F − anions will be constricted, thus leading to a lower conductivity (Figure 1d).…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, the F − transference number would be higher than 0.5. 6,23 This is consistent with the higher partial conductivity of F − anions than that of TMA + cations, as predicted by theoretic calculations (Table S1). In concentrated electrolytes, the movement of both TMA + cations and F − anions will be constricted, thus leading to a lower conductivity (Figure 1d).…”
supporting
confidence: 89%
“…Here, the cutoff charge capacity is set to prevent potentially undesired side reactions occurring at the electrode/ electrolyte interface. 23 As shown in Figure 3e,f, the CuF 2 //Pb@ PbF 2 full cell exhibits an initial discharge capacity of 109.9 mAh g −1 , which slowly increases to 134.8 mAh g −1 and finally delivers a capacity of 128.5 mAh g −1 after 160 cycles. These results indicate the excellent stability of WIS and its good suppressing capability toward CuF 2 dissolution.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The research on FIBs focused strongly on conversion-type cathode chemistries, i.e. metal/metal uorides (Me/MeF x ) [9][10][11][12][13][14][15] which offer the highest theoretical capacities due to the possibility of taking part in a multi-electron conversion process. For example, Fichtner et al 16 reported the use of CuF 2 as the conversion-type electrode material in FIBs.…”
Section: Introductionmentioning
confidence: 99%